International migrant workers in tourism and hospitality industry, Langkawi, Malaysia: does their demographic profile matter? - Mohd Shariff, Nurhazani; Zainol Abidin, Azlan; Mohd Bukhari, Azmil Munif (2019)
The main purpose of the study was to investigate the demographic profile of the employment of international migrant workers in the Langkawi tourism and hospitality industry. A total of 258 international migrant workers had participated in the study and the findings indicated that majority of them were male, with age ranged between 18 – 30 years old and were still single. Additionally, the findings also highlighted that the majority of the international migrant workers in Langkawi were semi-skilled and had the ability to speak good English. Most of them had migrated from Indonesia and had been working in the accommodation sector which was more towards customer service sectors. They also earned an income between RM1,000 – RM4,999 a month. The findings of the study would significantly assist the Workforce Department in designing and preparing a comprehensive policy regarding the employment of international migrant workers in Langkawi.